2008
DOI: 10.1038/nature07074
|View full text |Cite
|
Sign up to set email alerts
|

Archimedean-like tiling on decagonal quasicrystalline surfaces

Abstract: Monolayers on crystalline surfaces often form complex structures with physical and chemical properties that differ strongly from those of their bulk phases 1 . Such hetero-epitactic overlayers are currently used in nanotechnology and understanding their growth mechanism is important for the development of new materials and devices. In comparison with crystals, quasicrystalline surfaces exhibit much larger structural and chemical complexity leading, for example, to unusual frictional 2 , catalytical 3 or optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
195
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(201 citation statements)
references
References 29 publications
6
195
0
Order By: Relevance
“…Kink motion also occurs in experiments on colloidal particles moving over quasiperiodic substrates [39]. In addition, in studies of colloidal particles driven over corrugated 1D arrays, different dynamical transitions between pinned, smectic, and disordered flowing regimes were observed [33].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Kink motion also occurs in experiments on colloidal particles moving over quasiperiodic substrates [39]. In addition, in studies of colloidal particles driven over corrugated 1D arrays, different dynamical transitions between pinned, smectic, and disordered flowing regimes were observed [33].…”
Section: Introductionmentioning
confidence: 93%
“…Experiments and computational studies have shown that in the absence of a drive, a variety of orderings can arise for colloidal particles interacting with one-dimensional (1D) periodic substrates [13,32,33], two-dimensional (2D) periodic substrates [15,20,21,[34][35][36][37][38], 2D quasiperiodic substrates [39][40][41][42][43], or 2D random substrates [44]. While these studies have provided a better understanding of several features of commensurateincommensurate behaviors, being able to dynamically control the particle ordering and dynamics could lead to a variety of applications, including self-assembled structures, particle separation, and photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…S ince their discovery 1 , quasicrystalline phases have been found in 4100 intermetallic compounds, liquid crystals 2 , polymers 3 , colloids 4 and perovskite thin films 5 , and are recognized as universal phases of matter. A very important breakthrough was the discovery of stable intermetallic phases 6 , which enabled detailed experimental studies, including the determination of accurate atomic structures of quasicrystals and investigation of quasicrystalline surfaces and overlayers (ref.…”
mentioning
confidence: 99%
“…This strong dependence of superlubric behaviour on the substrate lattice spacing is in agreement with atomic friction force experiments on incommensurate surfaces 15,23 . We also carried out friction experiments on nonperiodic substrate potentials with quasiperiodic order, which are strongly incommensurate with the periodic monolayer 22 . Here, we find almost the same behaviour as for triangular substrates with s = 4.8 ÎŒm, which is consistent with the small friction coefficient on atomic quasicrystalline surfaces reported from experiments and simulations [24][25][26] .…”
mentioning
confidence: 99%
“…1a; ref. 22). To apply lateral forces to the colloidal crystal, the sample cell is translated with velocity u, which leads to a Stokes force F ∌ u acting on each particle (Methods).…”
mentioning
confidence: 99%